Dispersion of phenotypic variability of umbu tree in the Brazilian semiarid - Santos, Carlos Antonio Fernandes (Pesquisa Agropecuaria Brasileira, 1997)
Three hundred and fourty umbu trees (Spondias tuberosa A. Câm.) were characterized in 17 ecogeographic regions distributed in seven States of Northeast Brazil. The Agroecological Zoning of the Northeast and the information about extractivism of fruits of umbu tree were used to define the regions of sample. Twenty umbu trees were characterized in every ecogeographic region for 11 quantitative characters. The techniques utilized for all information were: principal components of correlations matrix and cluster analysis using the euclidian distance of the original standardized data and the nearest centroid sorting method. The trees were grouped in 17 clusters independently of the region of origin, evidencing that edafoclimatic difference and geographic distance did not interfere in the evolution and differentiation of umbu trees. The ecogeographic regions of Tanquinho, Jeremoabo and Ipupiara, Bahia State; Petrolina, Pernambuco State; and Pio IX, Piaui State, are indicated as points of dispersion or origin of umbu tree. Weight of fruit, diameter of canopy, diameter of fruit, weight of fruit peel and height of plant were the characters of less importance for discrimination of umbu tree.